Problem-Based Learning Model to Increase Students’ Critical Thinking - Dian Permatasari Kusuma Dayu; Cerianing Putri Pratiwi; Pratiwi Rahmah Hakim (Jurnal Basicedu, 2022)
This study aims to describe the application of problem-based learning (PBL) models to the critical thinking skills of 5th graders at Elementary School. The method used in this research is classroom action research. In this study, there are two data, namely verbal data and nonverbal data. The research subjects were elementary school students in grade 5 in the city of Madiun. The collecting data using observation techniques, interviews and tests. The instrument in this study used a questionnaire and a test. The data analysis technique in this research is quantitative and qualitative data analysis. Qualitative data analysis uses questionnaire data and observation, while quantitative data uses test results. The results of this study indicate an increase in students' critical thinking skills in thematic learning from cycle 1 and cycle 2. An increase in students' critical thinking skills in cycle I is 30%, students who pass the Minimum Completeness Criteria, and 60% of the second cycle in each cycle. The more students experience an increase in their critical thinking skills.